Relations between hepatobiliary scintigraphy findings and histopathological factors in patients with recurrent biliary colic. (14th May 2020) - Ahn, Hyein; Jang, Si‐Hyong; Lee, Hyun Ju; Lee, Ji‐Hye; Jung, Hae Il; Oh, Mee‐Hye; Lee, Sang Mi; Lee, Jeong Won
Abstract: Background/Purpose: The aim of the present study was to investigate the relationship between hepatobiliary scintigraphy findings and histopathological results in patients with recurrent biliary colic. Methods: We retrospectively enrolled 107 patients who underwent hepatobiliary scintigraphy for recurrent biliary colic and subsequent cholecystectomy. According to the hepatobiliary scintigraphy findings, patients were categorized into a nonvisualization of gallbladder activity (nonvisualized GB) group, low gallbladder ejection fraction (GBEF) group, and normal GBEF group. Differences in histopathologic factors between the three groups were evaluated and multivariate logistic regression analyses were performed to identify histopathological predictors for hepatobiliary scintigraphy findings. Results: The nonvisualized group had a higher frequency of patients with empyema and severe infiltration by neutrophils, lymphoplasma cells, and eosinophils. The low GBEF group had a higher muscle‐to‐total wall thickness ratio and muscle‐to‐fibrosis thickness ratio of the gallbladder wall than those in the normal GBEF group. On multivariate logistic regression analyses, severe degrees of lymphoplasma cell infiltration and eosinophil infiltration were independent predictors for nonvisualization of gallbladder activity, and a higher muscle‐to‐fibrosis thickness ratio was an independent predictor for low GBEF. Conclusions: In patients with recurrent biliary colic, nonvisualization of gallbladder activity on hepatobiliary scintigraphy was related to the degree of inflammation in the gallbladder, while low GBEF was related to muscular hypertrophy of the gallbladder. Abstract : Highlight Ahn and colleagues investigated the histopathological factors associated with hepatobiliary scintigraphy findings in patients with recurrent biliary colic. Nonvisualization of gallbladder activity on hepatobiliary scintigraphy was related to the degree of inflammation of the gallbladder wall, while a low gallbladder ejection fraction was related to muscular hypertrophy of the gallbladder.